RISK PERCEPTION ANALYSIS AND THE ENTREPRENEUR’S FINANCING DECISION - AHL-MAATALLAH, WIDAD; RIGAR, SIDI MOHAMED (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Researches on SMEs are treated from both strategic and entrepreneurial point of view. Based on these two perspectives our research aims to determine the position occupied by the risk perception in the financing decisions made by Moroccan entrepreneurs. By referring to prospect theory, Kahneman and Tversky (1979) defend the idea that the choice of the strategic decision in a context of uncertainty is intimately linked to the way in which risk is defined and perceived by the decision-maker. Our empirical study is conducted via the case study method, our results reveal that entrepreneurs integrate emotions, personal relationships, and common beliefs in their financing decisions, while the financial patterns just complete their choice, and do not determine it.